Methanosarcina acetivorans C2A topoisomerase IIIα, an archaeal enzyme with promiscuity in divalent cation dependence. - Raymond Morales; Palita Sriratana; Jing Zhang; Isaac K O Cann (PLoS ONE, 2011)
Topoisomerases play a fundamental role in genome stability, DNA replication and repair. As a result, topoisomerases have served as therapeutic targets of interest in Eukarya and Bacteria, two of the three domains of life. Since members of Archaea, the third domain of life, have not been implicated in any diseased state to-date, there is a paucity of data on archaeal topoisomerases. Here we report Methanosarcina acetivorans TopoIIIα (MacTopoIIIα) as the first biochemically characterized mesophilic archaeal topoisomerase. Maximal activity for MacTopoIIIα was elicited at 30-35°C and 100 mM NaCl. As little as 10 fmol of the enzyme initiated DNA relaxation, and NaCl concentrations above 250 mM inhibited this activity. The present study also provides the first evidence that a type IA Topoisomerase has activity in the presence of all divalent cations tested (Mg(2+), Ca(2+), Sr(2+), Ba(2+), Mn(2+), Fe(2+), Co(2+), Ni(2+), Cu(2+), Zn(2+) and Cd(2+)). Activity profiles were, however, specific to each metal. Known type I (ssDNA and camptothecin) and type II (etoposide, novobiocin and nalidixic acid) inhibitors with different mechanisms of action were used to demonstrate that MacTopoIIIα is a type IA topoisomerase. Alignment of MacTopoIIIα with characterized topoisomerases identified Y317 as the putative catalytic residue, and a Y317F mutation ablated DNA relaxation activity, demonstrating that Y317 is essential for catalysis. As the role of Domain V (C-terminal domain) is unclear, MacTopoIIIα was aligned with the canonical E. coli TopoI 67 kDa fragment in order to construct an N-terminal (1-586) and a C-terminal (587-752) fragment for analysis. Activity could neither be elicited from the fragments individually nor reconstituted from a mixture of the fragments, suggesting that native folding is impaired when the two fragments are expressed separately. Evidence that each of the split domains plays a role in Zn(2+) binding of the enzyme is also provided.